2016
DOI: 10.5194/bg-13-5065-2016
|View full text |Cite
|
Sign up to set email alerts
|

Using present-day observations to detect when anthropogenic change forces surface ocean carbonate chemistry outside preindustrial bounds

Abstract: Abstract. One of the major challenges to assessing the impact of ocean acidification on marine life is detecting and interpreting long-term change in the context of natural variability. This study addresses this need through a global synthesis of monthly pH and aragonite saturation state ( arag ) climatologies for 12 open ocean, coastal, and coral reef locations using 3-hourly moored observations of surface seawater partial pressure of CO 2 and pH collected together since as early as 2010. Mooring observations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 64 publications
5
64
0
Order By: Relevance
“…The seasonal range of surface seawater p CO 2 at mean SST and DIC are higher at KEO and Papa compared to WHOTS and Stratus (Figure a). Similar patterns between sites were found in observations of sea surface pH and aragonite saturation state [ Sutton et al , ]. This difference is attributed to larger seasonality of SST and productivity compared to the oligotrophic subtropical waters where WHOTS and Stratus reside.…”
Section: Resultssupporting
confidence: 84%
“…The seasonal range of surface seawater p CO 2 at mean SST and DIC are higher at KEO and Papa compared to WHOTS and Stratus (Figure a). Similar patterns between sites were found in observations of sea surface pH and aragonite saturation state [ Sutton et al , ]. This difference is attributed to larger seasonality of SST and productivity compared to the oligotrophic subtropical waters where WHOTS and Stratus reside.…”
Section: Resultssupporting
confidence: 84%
“…The x CO 2 measurement was made by a LI‐820, LI‐COR gas analyzer calibrated with reference gases traceable to World Meteorological Organization standards. A Sea‐Bird Electronics 16 plus V2 SeaCAT was also deployed and integrated with the MAPCO 2 system to make SST and SSS measurements used to calculate pCO 2 (Dickson et al, ; Sutton et al, ; Weiss, ). The accuracy of measuring the SST and SSS was about ±0.02 °C and ±0.02 psu, respectively (McPhaden et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…To help resolve this problem, high-resolution monitoring of seawater partial pressure of CO 2 (pCO 2 sw) on surface buoys in coastal regions began late in 2005 (see Massaro et al, 2012). Ocean carbonate chemistry research conducted in various coastal settings (Drupp et al, 2011(Drupp et al, , 2013Yan et al, 2011Yan et al, , 2016Massaro et al, 2012;Bates et al, 2014;Sutton et al, 2014aSutton et al, , 2016 has shown that, in order to understand the drivers of natural variability and identify longterm trends, it is necessary to gain better insight into the processes that control marine CO 2 concentrations, including the direction and magnitude of the air-sea CO 2 flux.…”
Section: Introductionmentioning
confidence: 99%